The Association Between Alcohol-Flavoured Non-Alcoholic Beverages and Alcohol Use in Japanese Adolescents. (25th October 2016) - Kinjo, Aya; Imamoto, Aya; Ikeda, Maki; Itani, Osamu; Ohida, Takashi; Kaneita, Yoshitaka; Kanda, Hideyuki; Tanihata, Takeo; Higuchi, Susumu; Osaki, Yoneatsu
Abstract: Aims: There are no legal regulations in Japan governing minors' consumption of alcohol-flavoured non-alcoholic beverages (AFNAB); therefore, we examined if their consumption could lead to increased alcohol use among adolescents in Japan. Methods: This cross-sectional study used a nonclinical, nationally representative sample of 38, 494 junior (19, 662 boys) and 61, 556 senior (31, 925 boys) high school students recruited in 2012. We measured AFNAB consumption rates and the order that adolescents first consumed AFNAB and alcohol. Results: The AFNAB consumption was strongly associated with alcohol use in high school students. Among all age groups, alcohol was more commonly consumed before AFNAB for both males and females. Conclusions: Consumption of AFNAB is more prevalent among minors than alcohol consumption and it has a strong association with alcohol consumption. However, concerns that AFNAB use would lead to increased alcohol use were not supported because AFNAB consumption usually started after adolescents began consuming alcohol. Short Summary: Consumption of AFNAB is more prevalent among high school students than alcohol consumption and it has a strong association with alcohol consumption. However, concerns that AFNAB use would lead to increased alcohol use were not supported because AFNAB consumption usually started after adolescents began consuming alcohol.